Enhancement of Digitalization in the "Bawah Bingin" Tourism Area Based on Website and Social Media - Abna Hidayati; Alwen Bentri; Eldarni Eldarni; Fetri Yeni J; Jasrial Jasrial; Vevi Sunarti (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2026)
This community service activity aims to provide assistance with digitalization and knowledge about tourism awareness in Nagari Sungai Aur, Pasaman Barat Regency. The main focus of the community service is the development of a website and social media as a marketing strategy for the integrated tourist area "Bawah Bingin," which is the new icon of the nagari. The priority issue faced is the lack of digital promotion and the palm oil-based creative economy center that has not been optimally managed. Thru this assistance, the service team from Universitas Negeri Padang (UNP) conducts training in content creation, digital marketing, and support for local MSMEs to optimize promotion. The expected outcomes of this program are the formation of a tourism-aware community, the development of integrated tourist areas, and the increase in community income in line with the Sustainable Development Goals (SDGs) targets.